Healthy Living for Elders: Tips for Remembering Your Medication - Linda B. Bobroff (EDIS, 2004)
Medications can help control a number of diseases and conditions. But they only work when we remember to take them! Select tips from the ones listed in this leaflet to help you remember to take your medication. This document is one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: March 2004.